The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3945/jn.111.145854
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Iron from Ferritin Is Independent of Heme Iron and Ferrous Salts in Women and Rat Intestinal Segments3

Abstract: Ferritin iron from food is readily bioavailable to humans and has the potential for treating iron deficiency. Whether ferritin iron absorption is mechanistically different from iron absorption from small iron complexes/salts remains controversial. Here, we studied iron absorption (RBC (59)Fe) from radiolabeled ferritin iron (0.5 mg) in healthy women with or without non-ferritin iron competitors, ferrous sulfate, or hemoglobin. A 9-fold excess of non-ferritin iron competitor had no significant effect on ferriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 37 publications
(55 reference statements)
3
65
1
Order By: Relevance
“…Endocytosis of the ferritin molecule is a highly efficient mechanism for the absorption of hundreds or thousands of dietary iron atoms per endocytic event (54). Knowledge on the cellular and molecular structures associated with this process becomes relevant to understand this new route of body iron acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocytosis of the ferritin molecule is a highly efficient mechanism for the absorption of hundreds or thousands of dietary iron atoms per endocytic event (54). Knowledge on the cellular and molecular structures associated with this process becomes relevant to understand this new route of body iron acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study demonstrated that ferritin iron is absorbed from the intestinal lumen by a process different from heme and inorganic iron absorption, and, once it is absorbed, it behaves as a slow-release iron donor (54). Vertebrate and plant ferritins consist of 24 ␣-helical subunits of H-and L-ferritin that assemble to form a hollow shell with an outer diameter of 12 nm and an inner diameter of 8 nm (12).…”
mentioning
confidence: 99%
“…It is absorbed intact, efficiently escorting about 1000 iron atoms into the body simultaneously, rather than one by one like heme iron. 54 Absorption of plant ferritin varies from 22% to 34% in various studies. 43 Plant ferritin, along with other plant sources of iron in a varied diet, can provide adequate iron in reasonable amounts.…”
Section: Clinical Research Reportsmentioning
confidence: 99%
“…Recent studies show that plant ferritin is a significant and readily available source of dietary iron. 54 Plant ferritin is absorbed independently through a separate transport system so it does not compete with other dietary sources of iron. It is absorbed intact, efficiently escorting about 1000 iron atoms into the body simultaneously, rather than one by one like heme iron.…”
Section: Clinical Research Reportsmentioning
confidence: 99%
“…Suggestions for other molecular mechanisms of ferritin absorption have also appeared (Theil et al 2012;Kalgaonkar and Lönnerdal 2009). Discussion on their receptor-mediated endocytosis in the intestines (Theil et al 2012), independence from the heme and ferrous salt absorption (Lucca et al 2001), as well as the questions about degradation during the food production processes prompt us to undertake studies on the ability of phytoferritin to survive in different cereal products, subjected to various types of treatment technology. The protein has unusual properties: it is resistant to many hydrolytic enzymes and temperature (up to 85°C) (Lönnerdal 2003;Liu and Theil 2005;Hoppler et al 2008).…”
Section: Introductionmentioning
confidence: 99%